Best Answer

-2x = -4x + 24

-2x + 4x = 24

2x = 24

x = 24/2

x = 12

Q: How can you solve -2x equals -4x plus 24 step by step?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

7x+6 = -3x-24 7x+3x = -24-6 10x = -30 x = -3

3w + 4 = 24 .......- 4... - 4 .......3w = 20 .......÷3 ...÷3 .........w = 20/3 or 6.6667

24 + 24 + 24 + 24 = 24 x 4 = 96

Thirteen plus thirteen.

24 + 14 = 38

Related questions

24

2z+6z+24=0 8z+24=0 8z= -24 z= - 3

5x+3+x=24 6x+3=24 6x=21 x=3.5

To solve for x you would first subtract 24 from each side. You would then divide both sides by 2. The answer is x=(y-24)/2

15 + n = 24 (subtract 15 from both sides) n = 9

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4

5 plus 25 equals 60. Need to solve for 5 plus 25 equals ?: 2 plus 10 equals 24 is equivalent to 2 × (1 plus 5) equals 2 × (12); and 3 plus 15 equals 36 is equivalent to 3 ×(1 plus 5) equals 3 × (12); thus 5 plus 25 equals ? is equivalent to 5 × (1 plus 5) equals 5 × (12); thus ? = 5 × 12 = 60.

7x+6 = -3x-24 7x+3x = -24-6 10x = -30 x = -3

2x/3 = 8 + 4x2x = 24 + 12x-24 = 10x-2.4 = x

4368/24 = 182 24 x 14 x 13 = 4368

To solve for x: 2x2 + 10 = 58 2x2 = 48 x2 = 24 x = √24 x = √4 × √6 x = 2√6

3w + 4 = 24 .......- 4... - 4 .......3w = 20 .......÷3 ...÷3 .........w = 20/3 or 6.6667